Both Directions at Once: John Coltrane, the sonic philosopher of oppositions - Banker, Bryan (Jazz Research Journal, 2022)
In Both Directions at Once, an album lost for almost 40 years, John Coltrane presents a constellation of musical tradition, themes, composition and improvisation, in dialectical opposition. This article imagines Coltrane as a sonic philosopher of oppositions and the album—named after Coltrane’s quote in which he attempts ‘starting a sentence in the middle, and then going to the beginning and the end of it at the same time… both directions at once’—as his philosophical treatise. Borrowing from biographers, musicologists and jazz critics, this contribution argues that in the album, the music engages with itself rather than seeking resolution or finality. In other words, Coltrane’s dialectical aesthetic drives the aesthetic. Both Directions at Once is sound focused on sonically opposing forces. It is an attempt by a deep thinker to present contradictions and oppositions between musical polarities that may create new potentialities. What listeners hear is Coltrane, the philosopher, striving toward a multidirectional aesthetic that furnishes music unshackled from the conditions of possibility.